Optimization of structural and operational parameters for the multi-size sinter vertical waste heat recovery with the objective of the income exergy - Zhang, Sizong; Huang, Linjing; Liu, Xiaohong; Wang, Hui (Frontiers in Energy Research, 2023)
To be consistent with the actual production, this paper establishes the 2-D steady-state mathematical model of the porous media to numerically analyze influences of structural and operational parameters on the vertical cooling process by applying particle characteristic parameters, and heat transfer and resistance correlations of the multi-size sinter. Considering comprehensive effects of the temperature and pressure drop, the operating and structural parameters are optimized with the objective of the maximum income exergy of the gas. Results show that the numerical model established in this paper can well predict the gas-solid heat transfer process in the sinter bed with the maximum error of 7%. Besides, the income exergy of the gas increases and decreases with the sinter outlet temperature and gas outlet temperature increasing, respectively. The reduction in the equivalent particle diameter is conducive to improving the income exergy. What’s more, the income exergy of the gas first ascends and then descends with the increase of the flow rate ratio of gas to sinter and the height of the sinter layer. Therefore, optimal values of the flow rate ratio of the gas to sinter and the height of the sinter layer are 1,050–1,540 m3·h−1 and 7–11.5 m within the scope of this study, respectively.